On the Correction of Spatial and Statistical Uncertainties in Systematic Measurements of 222Rn for Earthquake Prediction - Kulahci, Fatih; Sen, Zekai (Springer, 2014)
In earthquake prediction studies, the regional behaviour of accurate Rn-222 measurements at a set of sites plays a significant role. Here, measurements are obtained using active and passive radon detector systems in an earthquake-active region of Turkey. Two new methods are proposed to explain the spatial behaviours and the statistical uncertainties in the Rn-222 emission measurements along fault lines in relation to earthquake occurrence. The absolute point cumulative semivariogram (APCSV) and perturbation method (PM) help to depict the spatial distribution patterns of Rn-222 in addition to the joint effects of the K (dr), the radon distribution coefficient, and the perturbation radon distribution coefficient (PRDC). The K (dr) coefficient assists in identifying the spatial distributional behaviour in Rn-222 concentrations and their migration along the Earth's surface layers. The PRDC considers not only the arithmetic averages but also the variances (or standard deviations) and the correlation coefficients, in addition to the size of the error among the Rn-222 measurements. The applications of these methodologies are performed for 13,000 Rn-222 measurements that are deemed to be sufficient for the characterization of tectonics in the Keban Reservoir along the East Anatolian Fault System (EAFS) in Turkey. The results are evaluated for the A degrees double dagger me earthquake (M (L) 5.4, 5.7 km, 23 June 2011), which occurred in the vicinity of the EAFS.
Keywords: Earthquake prediction; Cumulative semivariogram; Fault line; Earthquake precursors; Radon observations; Spatial analysis of observed variations